Differential expression of TNFR1 (CD120a) and TNFR2 (CD120b) on subpopulations of human monocytes - Hijdra Daniëlle; Vorselaars Adriane DM; Grutters Jan C; Claessen Anke ME; Rijkers Ger T (BMC, 2012)
Abstract Background Three subpopulations of monocytes can be distinguished in human blood: classical (CD14++CD16−), intermediate (CD14++CD16+), and nonclassical (CD14+CD16++). CD16 expressing monocytes are expanded in patients with sarcoidosis and in various other inflammatory diseases. In sarcoidosis, it is unclear whether either intermediate, nonclassical or both CD16 expressing monocytes are responsible for this increase. Data relating to the monocyte subpopulations is receiving increasing attention, but the expression of TNF receptors on these subpopulations has not been studied thus far. The aim of this study was to determine frequencies of monocyte subpopulations and their expression of TNFR1 and TNFR2 in both sarcoidosis patients and healthy controls. Methods Peripheral blood cells of sarcoidosis patients and healthy controls were stained for the markers HLA-DR, CD14, CD16, CD120a and CD120b. Cells were measured on a FACSCalibur and analyzed with FlowJo. We used Student's t-test and a parametric One-way ANOVA for statistical analysis. Results Sarcoidosis patients had a significant higher frequency of intermediate monocytes than healthy controls. Significant differences in TNF receptor expression were found between the monocyte subpopulations, both in sarcoidosis patients as well as in healthy controls: intermediates expressed more TNFR1 than classicals and nonclassicals and nonclassicals expressed more TNFR2 than intermediates, whereas intermediates showed higher expression than classicals. Conclusions In both sarcoidosis patients and healthy controls intermediate monocytes show the highest expression level of TNFR1 among monocyte subpopulations and nonclassical monocytes show the highest expression level of TNFR2. These findings, as wells as the higher frequency of intermediate monocytes in sarcoidosis patients, provide evidence for the existence of two functionally-distinct CD16 expressing monocyte subpopulations.